Hubungan Pengetahuan Ibu Tentang Tumbuh Kembang Balita Dengan Deteksi Dini Gangguan TumbuhKembang Balita Di Posyandu Desa Bangun Rejo Kecamatan Tanjung MorawaTahun 2023 - Indra Agussamad; Martaulina Sinaga; Lisdayanti Simanjuntak; Petra Diansari Zega; Vinsen Julius Daud Ndruru; Lisna Rama Yanti Ndraha (Pusat Riset dan Inovasi Nasional, 2023)
In Indonesia, 8% of pre-school children experience speech and language disorders. Almost 20% of 2 year old children have speech delays and language disorders, speech delays most often occur at ages 3-16 years. The research method is correlative with a cross sectional approach. Sampling used a total sampling technique, namely where samples were taken from the entire population, namely 67 mothers with toddlers. Data collection in this research used primary and secondary data. Data analysis was carried out univariate and bivariate using the chi-square test. Mothers' knowledge in the good category regarding growth and development was 26 respondents (38%). Mothers' knowledge in the poor category regarding growth and development was 41 respondents (61%). Able to detect growth and development disorders in toddlers, namely 30 respondents (44%) The statistical test results with a p-value of 0.023 < 0.05 and OR= 4.26 so that the alternative hypothesis is accepted, which means there is a significant relationship between the relationship between mother's knowledge about toddler growth and development. early detection of growth and development disorders for toddlers at Posyandu, Bangun Rejo village, Tanjung Morawa sub-district. The results of this research are to increase mothers' knowledge and insight regarding the growth and development of toddlers so that they are better able to detect the growth and development of toddlers.